1998
DOI: 10.1128/jvi.72.7.6277-6277.1998
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Replication Capacity Rather Than In Vitro Macrophage Tropism Predicts Efficiency of Vaginal Transmission of Simian Immunodeficiency Virus or Simian/Human Immunodeficiency Virus in Rhesus Macaques

Abstract: We used the rhesus macaque model of heterosexual human immunodeficiency virus (HIV) transmission to test the hypothesis that in vitro measures of macrophage tropism predict the ability of a primate lentivirus to initiate a systemic infection after intravaginal inoculation. A single atraumatic intravaginal inoculation with a T-cell-tropic molecular clone of simian immunodeficiency virus (SIV), SIVmac239, or a dualtropic recombinant molecular clone of SIV, SIVmac239/1A11/239, or uncloned dualtropic SIVmac251 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…inoculation develop humoral immune responses, including neutralizing antibody (25,27), that were not observed in transiently viremic monkeys after intravaginal inoculation of SIVmac251. Third, SIVmac1A11 is not efficiently transmitted by intravaginal inoculation (29). Despite these observations, infection with an attenuated variant of SIVmac251 that is distinct from SIVmac1A11 remains a possible explanation for STV.…”
Section: Discussionmentioning
confidence: 99%
“…inoculation develop humoral immune responses, including neutralizing antibody (25,27), that were not observed in transiently viremic monkeys after intravaginal inoculation of SIVmac251. Third, SIVmac1A11 is not efficiently transmitted by intravaginal inoculation (29). Despite these observations, infection with an attenuated variant of SIVmac251 that is distinct from SIVmac1A11 remains a possible explanation for STV.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that R5 viruses undergo selective transmission across the genital mucosa [36], where epithelial cells selectively capture R5 viruses and transfer them to CCR5‐expressing target cells [37]. A number of studies have, however, found no correlation between R5 viruses and intravaginal transmission of either simian immunodeficiency virus or simian/human immunodeficiency viruses [38,39]. Whether DCs expressing C‐type lectins such as DC‐SIGN can play a role in virus transmission across the mucosal surfaces is still unknown, but this has been postulated as a potential mechanism of infection establishment [40].…”
mentioning
confidence: 99%
“…The present studies were designed to focus on the humoral responses generated during immunization and to determine the breadth of the protective response by challenging with a pathogenic simian-human immunodeficiency virus (SHIV) that contains an HIV-1-derived envelope. The challenge virus, SHIV 89.6PD , is highly infectious and causes a rapid pathology in macaques (25,28,34,40). It was constructed by using the SIV 239 molecular clone as the backbone with the substitution of the HIV-1 89.6 envelope gene for the SIV 239 envelope (35).…”
mentioning
confidence: 99%